The dual role of casein kinase 1, DTG1, in regulating tillering and grain size in rice - Jijin Li; Dan Zhou; Deke Li; Gen Wang; Rui Qin; Chengqin Gong; Kang Chen; Yunqing Tong; Lingfeng Li; Keke Liu; Jiangkun Ye; Binjiu Luo; et al. (Crop Journal, 2024)
Tiller number and grain size are important agronomic traits that determine grain yield in rice. Here, we demonstrate that DEFECTIVE TILLER GROWTH 1 (DTG1), a member of the casein kinase 1 protein family, exerts a co-regulatory effect on tiller number and grain size. We identified a single amino acid substitution in DTG1 (I357K) that caused a decrease in tiller number and an increase in grain size in NIL-dtg1. Genetic analyses revealed that DTG1 plays a pivotal role in regulation of tillering and grain size. The DTG1I357K allelic variant exhibited robust functionality in suppressing tillering. We show that DTG1 is preferentially expressed in tiller buds and young panicles, and negatively regulates grain size by restricting cell proliferation in spikelet hulls. We further confirm that DTG1 functioned in grain size regulation by directly interacting with Grain Width 2 (GW2), a critical grain size regulator in rice. The CRISPR/Cas9-mediated elimination of DTG1 significantly enhanced tiller number and grain size, thereby increasing rice grain yield under field conditions, thus highlighting potential value of DTG1 in rice breeding.